IMPLEMENTASI PEMBELAJARAN BERBASIS MASALAH PADA KURIKULUM 2013 DI SMK NEGERI 2 PADANG - Masril, Mardhiah; Jalinus, Nizwardi; Jama, Jalius; Dakhi, Oskah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of this study is to describe the problem-based learning situation in the implementation of the 2013 SMK curriculum and the learning situation after the implementation of Problem Based Learning (PBM). The approach of this research is a quantitative research using the ex post facto method and the data analyzed descriptively. The study was conducted in four majors at SMK Negeri 2 Padang. The population sample in this study was the educator who demonstrated the implementation of PBM in the implementation of the 2013 Curriculum. Information was collected with interview techniques and questionnaires by conducting Focused Group Discussions. Analyzing the data is done descriptively. This study obtained results, namely: a). PBM is so potentially carried out in the implementation of the 2013 curriculum in SMK. The stability of educators in the implementation of the 2013 curriculum is classified as very high, with an average value of around 95 and an achievement score of 72%. The accuracy of the implementation of learning in the implementation of the 2013 curriculum is classified as a very high category with an average of 153 and an achievement score of 79%. Of the 100 teachers or educators, 64 of them suggested that PBM was feasible to be implemented in all subjects in the implementation of the 2013 curriculum and b). PBM has been proven to add value to students' skills in terms of competencies, attitudes, and general and specific knowledge.